Managing Cities at Night : A Practitioner Guide to the Urban Governance of the Night-Time Economy - Acuto, Michele, 1984- (Book collections on Project MUSE., 2021)
Urban experts consider the future of night-time economies' governance during the pandemic and beyond in this scholarly and accessible guide. They use global case studies to illustrate a range of socio-economic issues in cities after dark, and investigate the role of public and private sectors and leaders in shaping urban planning and policy.